Factors affecting academic achievement of high achievers in Siraiki Area - Hafiz Muhammad Ather Khan; Jawed Hassaan Chandio; Riaz Hussain Sindhar; Nazakat Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
High academic achievement is desired by everyone but a few students are able to reach top position in their class. This study aimed to find out those factors which may be responsible for higher academic achievement of high achievers. The sample was taken from Khairpur Tame Wali and it was found there are a number of cultural factors among others which helped the students to secure higher positions in their classes. It is recommended in the end that children may be given equal opportunity to grow and they may be disciplined from early age to achieve higher goals in studies.
Keywords: 330; high achievers; Siraiki area; high academic achievement